Significados e valores das festas juninas - Silva, Elaine Maria Ultramare Ribeiro; Bento, Miriam Furtado; Schiavinato, Ricardo Leandro; Lima, Eliene Xavier de; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf